Doubts about the independence of Polish courts and international cooperation in criminal matters (Discourse of Law and Administration, 2023)
The article presents the latest developments with regard to the judicial reforms implemented in Poland since 2015 that have raised doubt whether the right to a fair trail can still be guaranteed. Focussing on the reforms‘ impact on the execution of European Arrest Warrants (EAW) issued by Polish authorities it outlines the relevant CJEU’s case law pertaining to this topic and its application in German court decisions on the refusal to execute Polish EAWs. Comparatively the article examines the CJEU’s ruling on German Prosecution Offices not being sufficiently independent from the power of the Minister for Justice to give instructions on individual cases in order to issue EAWs and describes the slow and ongoing process in Germany to change the current legal situation.
Keywords: European Arrest Warrant; Authority of Ministries of Justice in Germany to issue an instruction in a specific case to a Public Prosecutor; independence of justice